2015
DOI: 10.1590/1678-457x.0002
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous abscisic acid inhibits the water-loss of postharvest romaine lettuce during storage by inducing stomatal closure

Abstract: Postharvest lettuce often lose water, thus affecting both its market value and consumer acceptance. However, the mechanism of the water-loss is still waiting well exploration. The aim of the present study was to investigate the effect of a foliar application of ABA on the fresh weight-loss and the chlorophyll content of postharvest lettuce as well as its association with the regulation of stomata. The present data demonstrated that exogenously application of ABA, in a concentration range of 0 to 100 µM, signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…27 It was reported that exogenous ABA application can maintain a higher chlorophyll content, lower fresh weight loss, and reduce the transpiration rate by promoting stomatal closure in postharvest lettuce. 5 However, there are still some unsolved problems for ABA application, such as chemical instability, high expenses for production, and rapid catabolism by plant enzymes. 12 AM1 and AMF4 are structurally modified ABA- mimicking ligands capable of activating multiple ABA receptors and showing effects on preventing water loss from leaves and, thus, are promising for improving drought tolerance in agricultural crops.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…27 It was reported that exogenous ABA application can maintain a higher chlorophyll content, lower fresh weight loss, and reduce the transpiration rate by promoting stomatal closure in postharvest lettuce. 5 However, there are still some unsolved problems for ABA application, such as chemical instability, high expenses for production, and rapid catabolism by plant enzymes. 12 AM1 and AMF4 are structurally modified ABA- mimicking ligands capable of activating multiple ABA receptors and showing effects on preventing water loss from leaves and, thus, are promising for improving drought tolerance in agricultural crops.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it plays a vital role in reducing water transpiration by promoting stomatal closure . It was reported that exogenous ABA application can maintain a higher chlorophyll content, lower fresh weight loss, and reduce the transpiration rate by promoting stomatal closure in postharvest lettuce . However, there are still some unsolved problems for ABA application, such as chemical instability, high expenses for production, and rapid catabolism by plant enzymes .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations